Pituitary apoplexy mimicking meningoencephalitis: case report and scoping study. Issue 1 (1st January 2020) - Chu, Chun; Perilli, Gretchen A.; Judge, Casey; Sheng, Sen; Yacoub, Hussam A.
ABSTRACT: Background : Pituitary apoplexy (PA) is a rare but potentially life-threatening condition that may require urgent surgical intervention. Case Presentation : We report a case of a patient who was initially diagnosed with meningoencephalitis (ME) based on clinical presentation and cerebrospinal fluid (CSF) analysis, but was eventually diagnosed with PA. We present a summary of other cases reported in the literature of PA mimicking ME and analyze their clinical features and CSF findings. Results : Among all 22 PA cases reviewed, headache was the most commonly reported symptom. Hypopituitarism was seen in 94.4% of the cases; of these, panhypopituitarism was noted in 38.9%. The sensitivity of magnetic resonance image (MRI) for detecting PA was 94.7%, much higher than that of computed tomography (CT), which was only 31.6%. Neutrophil predominant pleocytosis was present in all cases with a neutrophil percentage ranging from 73% to 98%. CSF leukocyte count was less than 1000/ul in 86% of the cases. CSF erythrocytosis was seen in 92.9% of the cases with a count ranging from 15 to 2030/ul. Elevated CSF protein was present in all cases with a range of 69.8 to 239 mg/dl. CSF glucose level varied with a range between 12 and 136 mg/dl; the level was greater than 40 mg/dl in 73% of the cases. Conclusion : PA tends to be misdiagnosed as ME due to the similarities of semiology and CSF findings. PA should be considered in refractory acute headache cases, especially those with visual and endocrine abnormalities. Early recognition and treatment may lead to significant reduction in morbidity and mortality. Abbreviations: ACTH: adrenocorticotropic hormone; CSF: cerebrospinal fluid; CT: computed tomography; GRE: gradient echo; HRT: hormone replacement therapy;HSV: Herpes Simplex Virus; IV: intravenous; ME: meningoencephalitis; MRI: magnetic resonance image; PA: pituitary apoplexy; RBC: red blood cell; WBC: white blood cell